SAFETY LEADERSHIP CHARACTERISTIC OF SUPERVISOR PRODUCTION DIVISION AT PT. BCD - Prihatiningsih, Septyani (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: Work related accidents are one of the main focused and indicators of the successful implementation of Occupational Health and Safety (OHS) aspects in Indonesia. One of the causes of accidents is the worst implementation and supervision of OHS. Based on some research that has done, safety leadership is solution to improve OHS performance and reduce the number of work related accidents. PT. BCD is one of paper manufacturing company in Indonesia that using high-tech machinery and involving many workers who possibly increase risk of work related accidents. Purpose: Aims of this to identify safety leadership characteristics of supervisors Production Division at PT. BCD Method: This study uses descriptive qualitative research methods on supervisors in the Production Division of PT. BCD, one of paper manufacturing company in Karawang, West Java Province. Result: It has found that the characteristics of good safety leadership applied by the supervisor production division of PT. BCD is an element of commitment to OHS and communication. While the element of safety leadership characteristics that not well implemented, reflected by the element of safety involvement. Supervisors are not fully involved to safety program that consist of are involved in all corrective actions, and motivate the employee to participate in the OHS program. Conclusion: Safety leadership characteristics of supervisors in the Production Division of PT. BCD has not well implemented to the elements of safety involvement.